The Values of Independent Hip-Hop in the Post-Golden Era Hip-Hop's Rebels - Vito, Christopher; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"A necessary read for every researcher, historian, scholar and hip-hop fan that seeks to better understand independent hip-hop and aspires to rebel and utilize hip-hop as a tool of resistance." -DJ Kuttin Kandi, DJ, Artist, Organizer, and Activist "Christopher Vito has written an informative and compelling book on independent hip hop that examines how complexities of race, gender, class and sexuality are confronted within the genre. This book illuminates a subculture that is rarely explored, shining a light on independent hip-hop's power to counter mainstream ideology." -Ninochka McTaggart, PhD, Senior Researcher, Geena Davis Institute on Gender in Media, USA Utilizing a mixed-methods approach, this book uncovers the historical trajectory of U.S. independent hip-hop in the post-golden era, seeking to understand its complex relationship to mainstream hip-hop culture and U.S. culture more generally. Christopher Vito analyzes the lyrics of indie hip-hop albums from 2000-2013 to uncover the dominant ideologies of independent artists regarding race, class, gender, sexual orientation, and social change. These analyses inform interviews with members of the indie hip-hop community to explore the meanings that they associate with the culture today, how technological and media changes impact the boundaries between independent and major, and whether and how this shapes their engagement with oppositional consciousness. Ultimately, this book aims to understand the complex and contradictory cultural politics of independent hip-hop in the contemporary age.
Chapter1: Introduction -- Chapter 2: Just Say No to The Majors: Independent Hip-Hop Culture -- Chapter 3: Just Say No to 360s: Hip-Hop's Claim of Economic Exploitation -- Chapter 4: The Death of Indie Hip-Hop?: The Blurry Lines between the Majors and Independent Hip-Hop Music -- Chapter 5: Conclusions and Implications.
Keywords: Mass media; Culture; Political sociology; Music; Culture -- Study and teaching; Media Sociology; Sociology of Culture; Political Sociology; Music; Cultural Theory